Break Even Point Analysis As A Basic of Profit Planning In Handal Insan Sentosa Batik Business - Ucik Arfianti; Reswanda Reswanda (Yayasan Ahmar Cendekia Indonesia, 2020)
Batik is a craft that has high artistic value and has been a part of Indonesian culture for a long time. One of the centers of written batik in Sidoarjo is Reliable Insan Sentosa written batik which is a container in the effort to preserve batik itself. This study aims to analyze the amount of company revenue and production in the state of reaching Break Even Point. The method used in this study is a qualitative descriptive method, to get a clearer and more detailed picture based on the data and information that has been obtained. The results showed that the business of reliable handmade batik sentosa level of profit earned Rp. 12,182,325, where the break even point of sales achieved was Rp.199,000,000 with a total of 199 units. The achieved margin of safety is 10% or Rp.22,200,000 from sales. So that the margin of safety obtained is Rp.199,800,000. In this case the greater the margin of safety the better for the company because the company can experience a significant decline. MSMEs are advised to classify costs to prepare financial reports and apply a BEP analysis to determine financial condition.